PENGENALAN PAVING BLOCK DARI SAMPAH PLASTIK PADA MASYARAKAT PESISIR DI NEGERI TULEHU KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Silaban, Bernita br.; Rukua, Putri Kumalasari; Kaledupa , Marwa; Rilin; Molie , Jet Jeisen; Amir, Firda; Tabaika, Urfia (Universitas Mataram, 2024)
Plastic waste on the coast of Tulehu Country Salahutu District, Central Maluku is a problem that must be handled together. Plastic waste is often found washed up on coastlines and piled up around beaches. Lack of awareness and minimal information about how to process plastic waste into useful products is one of the causes, even though waste handling activities have been carried out. The solution offered in this service activity is to provide education about processing plastic waste into paving blocks. The aim of this activity is to provide understanding to the public about the importance of good waste management. Changing people's mindset in processing plastic waste into useful products. The methods used in this activity are survey, outreach, training and evaluation methods. Initial surveys and coordination were carried out to see field conditions and community habits. Socialization and training to enrich the material as well as evaluation to measure the level of understanding of the material provided. During this activity, the participants were very enthusiastic. This activity is new information for them. New participants learned that paving blocks can be made from plastic waste. Usually made from sand and cement. After socializing the processing of plastic waste into paving blocks, participants understood how to process plastic waste properly and correctly. The level of understanding of the material was measured by questionnaires given to participants before and after socialization and training. Before the activity, 95% of the people did not understand the material for making paving blocks and after the activity was carried out, 100% answered that they understood the material provided. Making paving blocks can be a solution to reducing plastic waste and can be developed into a new business source in Tulehu Country.